Self‐Healing Metallo‐Supramolecular Amphiphilic Polymer Conetworks. Issue 4 (13th January 2020) - Mugemana, Clément; Grysan, Patrick; Dieden, Reiner; Ruch, David; Bruns, Nico; Dubois, Philippe
Abstract: The current challenge in self‐healing materials resides in the design of materials which exhibit improved mechanical properties and self‐healing ability. The design of phase‐separated nanostructures combining hard and soft phases represents an attractive approach to overcome this limitation. Amphiphilic polymer conetworks are nanostructured materials with robust mechanical properties, which can be tailored by tuning the polymer composition and chemical functionality. This article highlights the design of phase‐separated nanostructured polymers from metallo‐supramolecular amphiphilic polymer conetworks, and their application for self‐healing surfaces. The synthesis of poly( N ‐(pyridin‐4‐yl)acrylamide)‐ l ‐polydimethylsiloxane polymer conetworks from the poly(pentafluorophenyl acrylate)‐ l ‐polydimethylsiloxane activated ester is presented. Loading of ZnCl2 salt into the phase‐separated polymer conetwork strengthens the network by cross‐linking the poly( N ‐(pyridin‐4‐yl)acrylamide) phases, while offering reversible interactions needed for self‐healing ability. Abstract : The current challenge in self‐healing materials resides in the design of materials, which exhibit improved mechanical properties and self‐healing ability. This article highlights the design of phase‐separated nanostructured polymers from poly( N ‐(pyridin‐4‐yl)acrylamide)‐ l ‐polydimethylsiloxane polymer conetworks. Loading of ZnCl2 salt into the phase‐separated polymer conetwork strengthens the network while offering reversible interactions needed for self‐healing ability.